Clinical analysis of primary small intestinal disease: A report of 309 cases - Zhan, Jun (World J Gastroenterol, 2004)
AIM: To evaluate the major clinical symptom, etiology, and diagnostic method in patients with primary small intestinal disease in order to improve the diagnosis. METHODS: A total of 309 cases with primary small intestinal disease were reviewed, and the major clinical symptoms, etiology, and diagnostic methods were analyzed. RESULTS: The major clinical symptoms included abdominal pain (71%), abdominal mass (14%), vomiting (10%), melaena (10%), and fever (9%). The most common disease were malignant tumor (40%). diverticulum (32%) and benign tumor (10%). Duodenal disease was involved in 36% of the patients with primary small intestinal diseases. The diagnostic rate for primary small intestinal diseases by double-contrast enteroclysis was 85.6%. CONCLUSION: Abdominal pain is the most common clinical symptom in patients with primary small intestinal disease. Malignant tumors are the most common diseases. Duodenum was the most common part involved in small intestine. Double-contrast enteroclysis was still the simplest and the most available examination method in diagnosis of primary small intestinal disease. However, more practical diagnostic method should be explored to improve the diagnostic accuracy.